Two-Dimensional Materials in Large-Areas: Synthesis, Properties and Applications - Zavabeti, Ali; Jannat, Azmira; Zhong, Li; Haidry, Azhar Ali; Yao, Zhengjun; Ou, Jian Zhen (Nano-Micro Letters, 2020)
Large-area and high-quality two-dimensional crystals are the basis for the development of the next-generation electronic and optical devices. The synthesis of two-dimensional materials in wafer scales is the first critical step for future technology uptake by the industries; however, currently presented as a significant challenge. Substantial efforts have been devoted to producing atomically thin two-dimensional materials with large lateral dimensions, controllable and uniform thicknesses, large crystal domains and minimum defects. In this review, recent advances in synthetic routes to obtain high-quality two-dimensional crystals with lateral sizes exceeding a hundred micrometres are outlined. Applications of the achieved large-area two-dimensional crystals in electronics and optoelectronics are summarised, and advantages and disadvantages of each approach considering ease of the synthesis, defects, grain sizes and uniformity are discussed. Highlights: 1 Two-dimensional materials including TMDCs, hBN, graphene, non-layered compounds, black phosphorous, Xenes and other emerging materials with large lateral dimensions exceeding a hundred micrometres are summarised detailing their synthetic strategies. 2 Crystal quality optimisations and defect engineering are discussed for large-area two-dimensional materials synthesis. 3 Electronics and optoelectronics applications enabled by large-area two-dimensional materials are explored.